High Arctic lakes reveal accelerating ecological shifts linked to twenty-first century warming - Emma Cameron; Marc Oliva; Dermot Antoniades (Scientific Reports, 2025)
Abstract The Arctic is among the most rapidly warming regions on Earth, and climate change has triggered widespread alterations to its cryosphere and ecosystems. Among these, high Arctic lakes are highly sensitive to rising temperatures due to the influence of ice cover on multiple limnological processes. Here, we studied the sediments of three lakes on northern Ellesmere Island (82.6°N), at the terrestrial limit of the Last Ice Area, to produce records of past environmental change. The colonization of the lakes by diatoms, as well as subsequent diversification and the appearance of planktonic forms, marked important ecological shifts due to warming temperatures and lengthening ice-free periods. A subsequent meta-analysis of 25 circumpolar diatom records revealed compositional shifts that paralleled those of temperature, including a notable acceleration since the turn of the twenty-first century that eclipses shifts previously observed since the mid-nineteenth century. Projections for sustained amplified warming imply that the accelerating changes we observed are likely to continue, as rising temperatures and lengthening ice-free seasons push Arctic lakes across further ecological thresholds.